The Effect of Depression Level on Quality of Life in the Elderly at Nursing Homes - Roihaana Alviatus Zahro; Zwasta Pribadi Mahardhika; Afrizal Tw; Liko Maryudhiyanto (Eduvest - Journal of Universal Studies, 2026)
As individuals age, they experience a natural decline in physical and cognitive function, increasing their vulnerability to various health problems, including depression. This condition may lead to reduced cognitive ability, diminished physical functioning, social withdrawal, poor sleep quality, and an elevated risk of suicide. Depression is more prevalent among older adults residing in nursing homes compared to those living with their families, and has been shown to negatively affect nearly all dimensions of quality of life. In Islamic teachings, caring for the elderly is a moral and spiritual obligation that emphasizes respect, compassion, and the fulfillment of their rights. This study aims to analyze the effect of depression level on the quality of life of older adults living in nursing homes and to examine these findings from an Islamic perspective. A quantitative cross-sectional design was employed, involving 77 respondents selected through simple random sampling. Of these, 16 respondents experienced depression and 5 were identified as having poor quality of life. The chi-square test yielded a p-value of 0.000, indicating a statistically significant association between depression level and quality of life. These findings highlight the impact of depression on the well-being of older adults and underscore the importance of providing humane, person-centered care aligned with religious values.